Scoring Metrics in English and Malay Languages among Young Spellers as Predictors of Word Reading - Tang, Swee Gek (Universiti Malaysia Sarawak (UNIMAS), 2019)
The aim of this study was to investigate the relationship among three spelling scoring metrics, namely, words spelled correctly (WSC), correct letter sequences (CLS), and phonological coding (PC) in English and Malay. A total of 866 Year 1 (Grade 1 equivalent) students from 11 randomly selected public primary schools in Kuching, Sarawak, Malaysia participated in this study. The study showed that the scores from each scoring metric were highly correlated to each other in both English and Malay. Additionally, this study also determined which scoring metric best predicts word reading performance in English and Malay. From the multiple linear regression models, both CLS and PC were significant and feasible to predict the word reading performance. However, this study suggests that the CLS scoring metric, which can be easily learned, readily computed, and do not need to be specially tailored for these two languages can be effectively used to predict word reading performance. Furthermore, this study also examined the variability of the Year 1 students’ spelling outcome in both languages. The students’ spelling performance was on average better in the Malay language than the English language and they seemed to be able to capture the number of syllables in a word, but they did not necessarily get the phoneme(s) correct in both languages.